The Characters (Χαρακτῆρες) of the Glagolitic Alphabet: New Light on an Old Puzzle - Mathiesen, Robert (Slavistica Vilnensis, 2020)
The article calls attention to a neglected source for the over-all “look and feel” of the Glagolitic alphabet as it was first created by Constantine the Philosopher circa 863 ad. This source is the variant forms of the Greek and other alphabets (including Hebrew and Arabic) that consist of so-called Brillenbuchstabe (otherwise charactères à lunettes or ring-letters). These variant alphabets were employed chiefly for esoteric purposes, including astrological and magical ones. Because of their limited use, they have largely been overlooked in standard handbooks of Greek and Oriental paleography. An interest in such subjects as astrology and magic comports poorly with routine assumptions about the inner lives of Medieval Saints such as Constantine. Relying on the extant primary sources for Constantine’s life, however, the article shows that his education, interests and mystical inclinations make a familiarity with some of these esoteric alphabets virtually certain. Thus it is historically plausible that such alphabets were among the inspirations for the general style, that is, the “look and feel”, of the letters of Constantine’s original glagolitic alphabet. (This article supplements the author’s earlier study from 2014, “A New Reconstruction of the Original Glagolitic Alphabet”.)
Keywords: Glagolitic alphabet; Constantine-Cyrill the Philosopher; ring-letters; Medieval Mysticism